Synthesis, Structure, and Reactivity of Ruthenium and Osmium Nitrido Complexes with 1,2-Benzenedithiolate Ligands: N- versus S-Alkylation. - Sellmann, Dieter; Wemple, Michael; Donaubauer, Wolfgang; Heinemann, Frank Wilhelm (Inorganic Chemistry, 1997)
The reactivity of the nitrido complexes (N(n)Bu(4))[Ru(N)(S(2)C(6)H(4))(2)] (1) and (N(n)Bu(4))[Os(N)(S(2)C(6)H(4))(2)] (2) (C(6)H(4)(SH)(2) = 1,2-benzenedithiol) toward electrophiles, R(+) (R = Me, Et, Ph(3)C), is described. While 1 yielded intractable mixtures of products, 2 could be cleanly alkylated. The synthesis of 1 has been reported previously (Z.Naturforsch. 1987, 42B, 341); complex 2 can be synthesized by treating (N(n)Bu(4))[Os(N)Cl(4)] with deprotonated 1,2-benzenedithiol in acetone/MeOH at 0 degrees C. Complexes 1 and 2 are isostructural and crystallize in the orthorhombic space group Pna2(1), Z = 8, with a = 36.881(6) Å, b = 9.402(2) Å, and c = 17.652(2) Å for 1 and a = 37.042(4) Å, b = 9.375(2) Å, and c = 17.671(2) Å for 2. The anions of both compounds consist of a five-coordinate mononuclear center with a distorted square-pyramidal geometry; a terminal nitrido ligand occupies the apical position and two chelating (S(2)C(6)H(4))(2)(-) ligands form the basal plane. Treatment of 2 with R(3)OBF(4) in CH(2)Cl(2) yields [Os(N)(S(2)C(6)H(4))(SC(6)H(4)SR)] (R = Me, 3; R = Et, 4) where one thiolate donor is alkylated. Alkylation of the sulfur of the 1,2-benzenedithiolate ligand was confirmed by NMR spectroscopy and X-ray crystallography (for 3). Complex 3.CH(2)Cl(2) crystallizes in the orthorhombic space group P2(1)2(1)2(1), Z = 4, with a = 8.551(1) Å, b = 10.772(2) Å, and c = 19.716(3) Å. In contrast, treatment of 2 with Ph(3)CPF(6) in CH(2)Cl(2) yields [Os(NCPh(3))(S(2)C(6)H(4))(2)] (5), whose (1)H and (13)C NMR spectra indicate that the terminal nitride is the site of electrophilic attack. X-ray crystallography further confirms the alkylation at the nitrogen atom; complex 5 crystallizes in the triclinic space group P&onemacr;, Z = 2, with a = 9.338(8) Å, b = 10.001(3) Å, c = 16.280(6) Å, alpha = 75.88(3) degrees, beta = 74.29(6) degrees, and gamma = 69.55(5) degrees.